Opportunities to Learn and Practise English as an L2 in Parent–Child Conversations. Issue 3 (1st September 2016) - Pinter, Annamaria
Abstract: This article explores a less formal learning context: interactions between parents and children using English as a second language (L2). In this study, L2-speaking parents were invited to conduct informal interviews at home with their own children about the children's experiences in local schools. The data indicated that the hybrid role of acting both as a parent and as an L2 teacher in these interactions led to excellent opportunities for the children to learn and practise their L2 competence. Parents initiated and controlled the topics and followed an Initiation–Response–Feedback discourse pattern, teaching new works and phrases, and scaffolding their children's language use, just as L2 teachers do. At the same time there were also invaluable opportunities for the children to challenge and resist their parents' ideas, initiate their own views and make jokes due to the more familiar and symmetrical parent–child relationship. The dual role of parent/teacher was associated with a more fluid type of discourse in the end, which created a space for learning. These insights suggest that L2 teachers may wish to explore innovative ways in which home–school partnerships could be better exploited as a resource for learning.